Preparation of porous fused silica support with high UV transmittance for photocatalytic membrane reactors. Issue 2 (15th January 2022) - Liang, Ruofan; Song, Xiaojiao; Lin, Xiaoqing; Guan, Kang; Peng, Cheng; Wu, Jianqing
Abstract: A porous support with sufficient strength and high UV transmittance is of key importance for potential applications of the light conducting photocatalytic membrane reactors. In this work, we report a simple method for the preparation of amorphous fused silica support with boric acid as sintering aid. The effect of experimental conditions on sintering was investigated by orthogonal test. The effect of porosity and refractive index of pore medium on the UV transmittance of the supports was also studied. It is demonstrated that boric acid not only assists the sintering of the fused silica supports with short sintering time, but also inhibits the crystallization of cristobalite. Fused silica supports prepared at 1150 °C for 1 h show average porosity of 42.3%, bending strength of 14.9 MPa and UV transmittance as high as 64.2% in water. These properties make fused silica a good candidate as support for light conducting photocatalytic membrane reactors.